The Genus Anthoceros (Anthocerotaceae, Anthocerotophyta) in Central Mexico - Ibarra-Morales, Ariadna; Muñíz, María Eugenia; Valencia, Susana (Phytotaxa, 2015)
The anatomy and morphology of six species of Anthoceros found in central Mexico are described. Anthoceros hispidus is reported new to Mexico. A key to the species of the genus in the region is provided.